Bagea Product Development Analysis at UD. Baruasa Empowers Kendari City Using Quality Function Deployment (QFD) Method - Ikram Ikram; Sarinah Sarinah; Yusna Indarsih (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
This study aims to determine consumer satisfaction with the development of bagea product quality at UD. Baruasa left Kendari City by using the Quality Function Deployment (QFD) method. Determination of the research location purposively. Data collection was done by interview and documentation methods. The analytical method used is Quality Function Deployment (QFD). The results showed that the development of bagea product quality at UD. Baruasa Membiri using the QFD method, it was found that the priorities to be developed by the wishes and needs of customers, respectively, were: (1) Information on the nutritional value of bagea product packaging (8.70%), (2) Variants of bagea product types (8, 25%), (3) Attractive packaging design for bagea products (7.78%), (4) Affordable selling prices for bagea products (7.15%), (5) There are promotional media (7.12%), (6 ) Price compatibility with bagea product quality (6.39%), (7) No use of hazardous materials (6.36%),(8) Bagea product texture (6.27%), (9) Bagea product halal certificate and label (6.16%), (10) Bagea product taste (6.07%), (11) Special purchase price for bagea product (6.05%), (12) Bagea product quality (6.01%), ( 13) Color of bagea products (5.95%), (14) Expiration information (expiration date) (5.89%), and (15) Ease of getting bagea products (5.79%).